Gereja di Tengah Perubahan Sosial: Bagai Mana Menjaga Nilai - Nilai dalam Dunia yang Terus Berubah (International Forum of Researchers and Lecturers, 2025)
This article discusses the challenges and strategies of the church in facing the ever-changing times today while continuing to uphold Christian values. The author analyzes how globalization and shifts in cultural paradigms influence the role and relevance of the church in today's diverse society. The discussion includes the importance of theological and practical adaptation, as well as the necessity for visionary leadership to navigate the complexities of the modern world. The main objective is to identify transformative approaches that allow the church not only to maintain its spiritual integrity but also to continue contributing positively to shaping an evolving society, without losing its identity and eternal mission.